Synthesis and characterization of MCM-41 with different methods and adsorption of Sr2+ on MCM-41 - Yilmaz, Muge Sari; Ozdemir, Ozgul Dere; Piskin, Sabriye (SPRINGER, 2015)
Mesoporous silica MCM-41 was prepared by classical and ultrasound methods as an adsorbent for the removal of Sr2+ from aqueous solution. The physical properties of the synthesized materials were investigated by X-ray diffraction and Brunauer-Emmett-Teller analysis. The results showed that MCM-41 prepared by the classical method had higher specific surface area and pore volume than those prepared by the ultrasound method. Therefore, it was selected as an adsorbent for the investigation of adsorption isotherms and kinetics. Adsorption of Sr2+ to MCM-41 was strongly dependent on pH values. Three two-parameter (Langmuir, Freundlich, and Temkin) and two three-parameter (Redlich-Peterson and Koble-Corrigan) adsorption isotherms were employed to model the equilibrium data of Sr2+ on the mesoporous adsorbent. The results indicated that the adsorption isotherm data fitted better to the Freundlich isotherm than to the Langmuir, Temkin, Redlich-Peterson, and Koble-Corrigan isotherms. The experimental data was described very well by the pseudo-second-order kinetic model.
Keywords: MCM-41; Adsorption; Ultrasound; Isotherm; Strontium; MOLECULAR-SIEVES; AQUEOUS-SOLUTION; MESOPOROUS SILICA; REMOVAL; BEHAVIOR; ADSORBENT; TEMPLATE; KINETICS; SORPTION; Chemistry